Digital Storytelling as a Creative Teaching Method in Promoting Secondary School Students’ Writing Skills - Lim, Pei Rong; Md Noor, Norah (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Abstract - With the current needs of shaping 21st-century classroom in schools, the use of technology has now become compulsory for teachers to incorporate in the classroom. The exposure to technology is highly necessary for the current generation to prepare them for the future ahead. Digital storytelling is one of the tools available in the market for learning. There is no much research yet found in Malaysia that investigates the usefulness of the digital storytelling in promoting secondary school students’ writing skills. Therefore, this research tries to implement one digital storytelling tool in teaching Writing for English Form 1 and tries to identify the elements of digital storytelling tool that might be able to promote students’ writing skills. This research involved fifteen Form 1 students. The data was collected through four (4) time series tests in a pre-experimental research study. The students’ performance in each treatment were marked according to the Rubrics to Assess Digital Stories and were analysed using Friedman Ranks Test. The finding shows that there is an improvement in students’ performance after four treatments of using the Digital Storytelling tools. For the elements of digital storytelling tool that affected after using the digital storytelling tool, the student respondents always applied six elements: ‘Overall Purpose of the Story’, ‘Dramatic Questions’, ‘Choice of Content’, ‘Pacing of the Narrative’, ‘Quality of the Images’ and ‘Good Grammar and Language Usage’. Furthermore, there is an improvement in student respondents’ post-test marks after four treatments of using Storybird. The study shows a relationship between elements of digital storytelling tool in the four treatments and students’ writing performance in post-test. All of the elements shows a significant relationship with students’ writing performance except for ‘Dramatic Questions’.